2003
DOI: 10.1007/bf03405053
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Health

Abstract: Objective: The Canadian Public Health Association, along with other professional organizations, has identified intimate partner violence (IPV) as a priority health issue to which the health professions must respond. This study synthesizes Canadian studies on the prevalence of IPV against women, focusing in particular on the stated implications for women's health and health care. Methods: Medical and social science databases were searched for all articles pertaining to IPV in Canada for 1974 through September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…IPV occurring in the past year ranged from 4% to 54%. Within a Canadian context, Clark and Du Mont's (2003) systematic review of IPV prevalence studies found that 0.4% to 23.0% of Canadians are affected by IPV annually. Despite changes in policy that promote the ending of violence against women in North America (e.g., procharging and mandatory arrest policies), intimate partner violence continues to be a major risk factor threatening women's psychological and physical well-being.…”
Section: Violence Against Women 17(1)mentioning
confidence: 99%
“…IPV occurring in the past year ranged from 4% to 54%. Within a Canadian context, Clark and Du Mont's (2003) systematic review of IPV prevalence studies found that 0.4% to 23.0% of Canadians are affected by IPV annually. Despite changes in policy that promote the ending of violence against women in North America (e.g., procharging and mandatory arrest policies), intimate partner violence continues to be a major risk factor threatening women's psychological and physical well-being.…”
Section: Violence Against Women 17(1)mentioning
confidence: 99%
“…There has been a number of community studies, mostly from North America, that show that, on average, one in five couples experiences IPV over a 12month period (Field & Caetano, 2005). A review of 11 Canadian studies of IPV against women found annual prevalence figures ranging from 0.4% to 23.0% (Clark & Du Mont, 2003). In contrast, the Intimate Partner Violence Fact Sheet issued by the Centers for Disease Control and Prevention (CDC, 2000b) suggested that 0.8% of women and 0.1% of men aged 12 years and older experience an episode of IPV each year.…”
mentioning
confidence: 99%
“…Canadian prevalence data related to DV collected via the 1999 version of the Canada General Social Survey indicated that the last 5-year rates of DV increased among women for all types of violence except psychological violence ( Romans et al, 2007 ). A review of 11 Canadian studies reported annual prevalence rates of DV as varying from 0.4–23% ( Clark & Du Mont, 2003 ). Neither of these studies reported data specifically related to immigrant women.…”
mentioning
confidence: 99%